2014
DOI: 10.1186/1471-2180-14-27
|View full text |Cite
|
Sign up to set email alerts
|

Global secretome characterization of A549 human alveolar epithelial carcinoma cells during Mycoplasma pneumoniae infection

Abstract: BackgroundMycoplasma pneumoniae (M. pneumoniae) is one of the major etiological agents for community-acquired pneumonia (CAP) in all age groups. The early host response to M. pneumoniae infection relies on the concerted release of proteins with various biological activities. However, no comprehensive analysis of the secretory proteins has been conducted to date regarding the host response upon M. pneumoniae infection.ResultsWe employed the liquid chromatography-tandem mass spectrometry (LC-MS/MS)-based label-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 61 publications
(84 reference statements)
1
14
0
1
Order By: Relevance
“…Studies have shown that M. pneumoniae can invade A549 lung cancer cells, evidenced by its detection in the cytoplasm and nucleus, and the invasive ability depends on the duration and temperature of infection (24). In cell culture in vitro , M. pneumoniae has been shown to invade non-phagocytes, survive for >6 months and synthesize DNA inside cells (7).…”
Section: Direct Damage Mechanismsmentioning
confidence: 99%
“…Studies have shown that M. pneumoniae can invade A549 lung cancer cells, evidenced by its detection in the cytoplasm and nucleus, and the invasive ability depends on the duration and temperature of infection (24). In cell culture in vitro , M. pneumoniae has been shown to invade non-phagocytes, survive for >6 months and synthesize DNA inside cells (7).…”
Section: Direct Damage Mechanismsmentioning
confidence: 99%
“…With the aim to evidence differences between the two groups, this analysis resulted in the identification of 15‐lipoxygenase‐derived ω‐3 and ω‐6 oxylipins as the most prominent different components, thus suggesting their role in allergic inflammation. LC‐MS/MS was also applied by other authors: (i) to compare the level of lysophosphatidic acids (LPAs) in idiopathic pulmonary fibrosis patients versus healthy controls ; (ii) to identify novel biomarkers and pathological mediators of disorder in subjects after subsegmental exposure ; (iii) to characterize the global secretome of A549 human alveolar epithelial carcinoma cells during Mycoplasma pneumoniae infection ; (iv) to compare the proteomes of patients with moderate and stable chronic obstructive pulmonary disease (COPD) versus healthy controls and (v) to identify proteins that differentiate survivors from nonsurvivors of acute respiratory distress syndrome . This differentiation was also investigated by Evans et al.…”
Section: Analysis Of Human Fluids Collected By Invasive Methodsmentioning
confidence: 99%
“…The first involves engagement with the TLRs, notably TLR2 [128][129][130], leading to the up-regulation of IL-12, IFNγ and other pro-inflammatory cytokines [131,132]. Interestingly, Mycoplasma species infection leads to the generation of a wide range of DAMPs including those normally released following cellular necrosis [133]. Mycoplasma antigens are also capable of activating the inflammasome [134,135], with subsequent elevation of IL-1α, IL-18, and ROS levels and a concomitant decline in the mitochondrial membrane potential [136][137][138].…”
Section: Mycoplasmamentioning
confidence: 99%